Spesies dan Peran serangga Pengunjung Bunga Semangka (Citrullus lanatus Thunb). - Yulia Pujiastuti; R. Oktarida; H. Hamidson; Arsi Arsi (xxxx-xxxx, 2020)
Pujiastuti Y, Oktarida R, Hamidson H, Arsi A. 2020. Species and role of insect visiting watermelon flower (Citrullus lanatus Thunb). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Flower visitor insects play an important role, especially in pollination process of plants. The success of crop production depends largely on the success of  pollination process. The research objective was to study the role and behavior of flower-visiting insects in watermelons. The research was conducted at a fruit planting center in Indralaya Indah Village, Indralaya District, Ogan Ilir Regency, South Sumatra from June to August 2019. The study was conducted using purposive sampling method (selecting flowering watermelon plants) and observing insect behavior by using scan sampling (direct observation in the field) in the morning. The results of  observations obtained 4 orders, 8 families and 11 species. The insect orders found were Hymenoptera (4 families, 7 species), Lepidoptera (2 families, 2 species), Coleoptera (1 family, 2 species) and Diptera (1 family, 1 species). The order Hymenoptera dominates the flower-visiting insects with a role as a pollinator.